On the periodic solutions of a class of duffing differential equations - Llibre, Jaume; Roberto, Luci Any [UNESP] (American Institute of Mathematical Sciences (AIMS), 2013)
In this work we study the periodic solutions, their stability and bifurcation for the class of Duffing differential equation mathematical equation represented where C > 0, ε > 0 and Λ are real parameter, A(t), b(t) and h(t) are continuous T periodic functions and ε is sufficiently small. Our results are proved using the averaging method of first order.
Keywords: Averaging method; Bifurcation; Duffing differential equation; Periodic solution; Stability